The Influence Of Problem Financing and Liquidity On The Profitability Of Sharia Business Units (Period 2018-2022) - Ilham Saleh; Norvadewi; Nur Rahmatullah (International Journal of Management and Business Economics, 2023)
The research used in this research is a quantitative method, the data used is secondary data, namely quarterly financial reports for the 2018-2022 period obtained from the official OJK (Financial Services Authority) website. The population in this study is Sharia Business Units in Indonesia and the sample uses porposive sampling so that there are 3 Sharia Business Units as samples, namely PT Bank Tabungan Negara, PT BPD Yogyakarta, and PT BPD DKI. The data analysis method used is panel data regression analysis for processing research data using the Eviews version 12 statistical test tool. Hypothesis tests carried out are the F test, t test, and the Adjusted coefficient of determination. The results obtained in this research based on partial hypothesis testing are that the problematic financing variable has a significant negative effect on profitability, while liquidity has a significant positive effect on the profitability of sharia business units (UUS) for the 2018-2022 period. Simultaneously (f test) shows that simultaneously the NPF and FDR variables have a significant effect on ROA. This means that NPF and FDR contribute to the profitability of the Sharia Business Unit. The results of the determination test show that the profitability variable is influenced by the problematic financing and liquidity variables by 69.53%, while the remaining 30.47% is influenced by other variables outside this regression equation or variables that were not studied.